Balloon expandable aortic stent‐graft for the treatment of aortic aneurysm and rupture in a dog. Issue 6 (23rd September 2021) - Klainbart, Sigal; Segev, Gilad; Chen, Hilla; Peery, Dana; Shipov, Anna
Abstract: Objective: To describe the successful placement of an aortic stent graft in a dog suffering from aortic aneurysm and rupture. Case summary: A 4‐year‐old neutered female mixed breed dog weighing 25 kg was presented with a chief complaint of acute onset of weakness and respiratory distress. On presentation, the dog was lateral and unresponsive, hypothermic, tachycardic, and tachypneic. Pleural effusion was identified in the right hemi‐thorax on thoracic‐focused sonographic scan for trauma. Thoracic radiographs showed a fluid/soft tissue opacity in the cranial mediastinum and pleural effusion on the right side. Thoracocentesis yielded noncoagulating blood. Hematology revealed normal PCV and total plasma protein that decreased within 24 hours to 20% and 50 g/L (20%/5.0 g/dL), respectively. The dog was treated with IV fluids, tranexamic acid, and fresh frozen plasma. An aortic aneurysm with irregular mineralization of the right ventrolateral aortic wall was identified on computed tomography examination, which also demonstrated a peri‐aortic hematoma. A decision was made to attempt treatment with a stent graft. Under general anesthesia, a marker catheter was inserted into the esophagus. A 10‐Fr sheath was inserted into the right femoral artery, and an angiography catheter was advanced over a wire. After angiography, a stent graft (12‐mm × 50‐mm) was placed over the guide wire and deployed under fluoroscopic guidance. The dog recovered uneventfully, with no evidence of recurrent bleeding, and was discharged 2 days after the procedure with antimicrobials, anthelmintic, and antithrombotic treatment. At 90‐day follow‐up, the dog was doing well, and stent position was radiographically confirmed. New or unique information provided: This report describes successful management of aortic aneurysm and dissection, an uncommon and challenging pathology in the veterinary practice with few available treatment options. Stent graft placement is a minimally invasive procedure in which a covered stent is placed over the lesion to prevent rupture.